Question

( x+3>0 )
( x geq-3 )
( cos frac{pi}{2} )
( x^{2}+f_{1} 6 x-4 x-x^{2}+beta= )
( x^{2}+2 x=0 )
( begin{array}{l}x(x+2)=0 x-0 quad x=-2end{array}-(1 )
Cars II ( f quad x+3<0 quad x<3 )
( x^{2}+9+6 x+4 x+12+3=0 )
( x^{2}+10 x+24=0 )
( x^{2}+6 x+4 x+24=0 )
( x(x+6)+4(x+6)=0 )
( left(begin{array}{ll}x+6 & (x+4)=0 x= & -6end{array}, x=-4right. )
( begin{aligned} operatorname{sum}_{x} y_{1} frac{operatorname{sov} t}{1} &=frac{-6-4-2}{1-12} end{aligned} )

# .11 Sum of roots of the equation (x + 3)2 – 4 | x + 3 + 3 = 0 is- (A) 4 (B) 12 (D) - 4 (C) - 12

Solution